Richard Shusterman (2021). Ars Erotica: Sex and Somaesthetics in the Classical Arts of Love. Cambridge: Cambridge University Press - Villalba Cívico, Luis Miguel (Review of Anthropology and Philosophy of the Sacrum, 2024)
Reseña Richard Shusterman (2021). Ars Erotica: Sex and Somaesthetics in the Classical Arts of Love. Cambridge: Cambridge University Press